Insights from the study of high-temperature interface superconductivity - Panagopoulos, Christos (2013)
A brief overview is given of the studies of high-temperature interface superconductivity based on atomic-layer-by-layer molecular beam epitaxy (ALL-MBE). A number of difficult materials science and physics questions have been tackled, frequently at the expense of some technical tour de force, and sometimes even by introducing new techniques. ALL-MBE is especially suitable to address questions related to surface and interface physics. Using this technique, it has been demonstrated that high-temperature superconductivity can occur in a single copper oxide layer—the thinnest superconductor known. It has been shown that interface superconductivity in cuprates is a genuine electronic effect—it arises from charge transfer (electron depletion and accumulation) across the interface driven by the difference in chemical potentials rather than from cation diffusion and mixing. We have also understood the nature of the superconductor–insulator phase transition as a function of doping. However, a few important questions, such as the mechanism of interfacial enhancement of the critical temperature, are still outstanding.